Hubungan Pengetahuan, Sikap Ibu Nifas 0-3 Hari dengan Perilaku Pemberian Kolostrum pada Bayi Baru Lahir di Puskesmas Kecamatan Duren Sawit Jakarta Timur - Revie Fitria Nasution; Fitria Prihatini (Jurnal Persada Husada Indonesia, 2015)
Infancy period is a crucial time in the life cycle, especially at the age of 0-6 months because at this stage baby needs to adapt to its environment. Breastfeeding as the best baby food of God's creation, should not be replaceable by any other foods and beverages. Colostrum is the first stage liquid milk produced during pregnancywhich is rich with nutrients and immune substances. Colostrum has a high content of proteins, vitamins A, B1, B2, E and also contains minerals. The purpose of this researchis to analyze the correlation between knowledge and attitudes puerperal women in the decision giving her colostruma soon after the baby is born. This study is an observational analytic study with cross sectional design, located at Puskesmas District of Duren Sawit, East Jakarta, all population in this study are puerperal women who resides in the sub-district health center Duren Sawit, East Jakarta, the number of samples taken in this study were 60 respondents. Sample data in categorical scale was described in frequency and percent. To examine the differences in subject characteristics, Chi square test (χ2) was used. Bivariate analysis showed that the variables that proved to be related to the administration of colostrum to the newborn is the attitude with p = 0.000 and OR = 15.375; CI = 95%. Thus it can be concluded that attitude have a significant association with the administration of colostrum to the newborn. To motivate women to have a good attitude and positive behavior at the time of entering the post-partum period, it is necessary to increase the awareness and knowledge of mothers since pregnancy and Posyandu trainee about the benefits and advantages of giving colostrum soon after birth.